Dextrose Hydration May Promote Cisplatin-induced Nephrotoxicity in Rats: Gender-related Difference - Farzaneh Karimi; Sayyedehnikta Kasaei; Azar Baradaran; Farzaneh Ashrafi; Ardeshir Talebi; Zahra Lak; Mehdi Nematbakhsh (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUNDS: Cisplatin (CP) as an anticancer drug may affect the plasma glucose level while diabetic subjects are protected against CP-induced nephrotoxicity. In the current study, the role of dextrose hydration during CP therapy on CP-induced nephrotoxicity was evaluated.METHODS: Sixty-nine male and female rats were divided into 12 groups. The rats were hydrated with 15 mL/kg vehicle or different doses of 2%, 10% and 20% dextrose before and after 7.5 mg/kg CP administration. One week later, the biochemical and kidney function markers, and histology finding were determined.RESULTS: All the animals co-treated with CP and 20% dextrose, were dead during one week of the experiment. Administration of CP alone increased kidney tissue damage score (KTDS) and kidney weight (KW). It also elevated the blood urea nitrogen (BUN) and BUN-creatineine ratio (BUN/Cr) levels in the serum. In addition, CP decreased body weight and creatinine (Cr) clearance (ClCr) significantly in both male and female rats (p<0.05). However, 2% and 10% dextrose did not alter the mentioned parameters in male, but 10% dextrose supplement increased the serum levels of BUN, Cr and BUN/Cr ratio, KW and KTDS significantly in female rats (p<0.05).CONCLUSION: Our data suggest that not only do not support the nephro-protective role of dextrose hydration during CP therapy, the dextrose hydration can act as risk factor to promote CP-induced nephrotoxicity in female rats. Prohibition of high carbohydrate (glucose) diet during CP therapy is recommended.KEYWORDS: cisplatin, nephrotoxicity, dextrose, rat, gender